The Effect of Chronic Inflammation and Oxidative and Endoplasmic Reticulum Stress in the Course of Metabolic Syndrome and Its Therapy - Michalina Alicka; Krzysztof Marycz (Stem Cells International)
Metabolic syndrome (MetS) is highly associated with a modern lifestyle. The prevalence of MetS has reached epidemic proportion and is still rising. The main cause of MetS and finally type 2 diabetes occurrence is excessive nutrient intake, lack of physical activity, and inflammatory cytokines secretion. These factors lead to redistribution of body fat and oxidative and endoplasmic reticulum (ER) stress occurrence, resulting in insulin resistance, increase adipocyte differentiation, and much elevated levels of proinflammatory cytokines. Cellular therapies, especially mesenchymal stem cell (MSC) transplantation, seem to be promising in the MetS and type 2 diabetes treatments, due to their immunomodulatory effect and multipotent capacity; adipose-derived stem cells (ASCs) play a crucial role in MSC-based cellular therapies. In this review, we focused on etiopathology of MetS, especially on the crosstalk between chronic inflammation, oxidative stress, and ER stress and their effect on MetS-related disease occurrence, as well as future perspectives of cellular therapies. We also provide an overview of therapeutic approaches that target endoplasmic reticulum and oxidative stress.